(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The goal of sustainability is to satisfy current needs without jeopardizing the ability of future generations to satisfy their own demands. In the leather and footwear sectors, sustainability is defined as shoe design, development, manufacturing, distribution, and selling procedures that reduce the negative effects on the environment, conserve energy and natural resources, are secure for workers, communities, and customers, and are financially prudent. In this study, the scientific literature on innovation and sustainability in the footwear sector during the previous ten years will be analyzed. The study is in the descriptive and exploratory categories. The procedure produced 38 papers in the Scopus database and Google Scholar that matched the research topic. From 2000 to 2023, on the subject of leather and footwear, the bibliometric analysis identified the most pertinent papers, authors, keywords, nations, research institutions, and journals. For the purpose of bibliometric analysis, R Studio will be used. The leather and footwear industries must support each other in terms of innovation and sustainability, which we tried to find through a systematic literature review analysis. Innovation in the footwear industry is an important factor, and due to the reduction of raw materials such as leather and the negative impact of leather on the environment, the importance of sustainability in the footwear industry has increased.